Performance is Body, the Crisis is of the Body: Interviews with Remote Emergency Education Teachers (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
After a long study on performance approach in education, the pandemic calls into question not only the action research at school, but also and, fundamentally, the research’s theme. How to think about education through the body in pandemic times? The interview was the device created for the necessary research confrontation and positioning. The device performance is body the crisis is of the body serves to remind that the body not only unites the most diverse performance’s points of view, but is also at the center of the crisis we are experiencing. This article is the interviews with remote emergency education teachers result decanting.